Lipase Catalysed Transesterification Reactions of Triglycerides - Madhu, Katiyar (My University, 2014)
Fatty acid alkyl esters (FAAEs), commonly known as biodiesel, has emerged as environmental friendly and renewable substitute for the conventional diesel fuel, in recent past. Biodiesel at commercial scale is produced by the transesterification of triglycerides (animal fats or vegetable oils) in presence of chemical catalysts. Chemical catalysts due to their inherent disadvantages must be replaced with greener and renewable catalysts such as lipase. On the other hand slow rate of lipase catalyzed reactions and extremely high cost of pure enzyme has prohibited their application at industrial scale for biodiesel production. In this context, present work envisaged to enhance the activity and reusability of the of the commercially available lipases. The effect of alkali (Na+ and K+), alkaline earth (Ca+2 and Ba+2) and transition (Cr+3, Fe+3, Co+2, Cu+2 and Ni+2) metal ions on hydrolytic and transesterification activity of Candida rugosa lipase (CRL) and commercially available immobilized lipases (Lipozyme and Novozyme 435) was investigated. Out of the metal ions studied, Cr+3 and Co+2 were able to catalyze the activity of the pure lipase to the maximum extent. However, activity of the immobilized enzymes was not increased by the presence of metal ions. The kinetic of the lipase catalyzed reactions in presence of metal ions were also investigated. To improve the reusability and stability, lipase enzyme was immobilized by physical adsorption and entrapment techniques using mesoporous silica as a support material. Mainly three different types of support materials viz., MCM-41, SBA-15 and Ti/SiO2, were employed for the physical adsorption of lipase. The immobilized lipase has been characterized by powder X-ray diffraction, scanning and transmission electron microscopic and Fourier transform infrared studies. The immobilized enzyme was used as solid biocatalyst for the transesterification reactions of cotton seed oil with methanol. Physically adsorbed demonstrated poor reusability may be due to the denaturation of the enzyme while catalyzing the first catalytic cycle. On the other hand, Rhizomucor miehei lipase was entrapped in a single step with in silica particles having oleic acid core. Immobilized lipase was characterized by powder X-ray diffraction, scanning and transmission electron microscopy and Fourier transform infra-red studies. The immobilized enzyme was employed for the transesterification of the cotton seed oil with methanol and ethanol. Under the optimum reaction condition of methanol to oil molar ratio of 12:1, stirring speed of 250 rpm at 40 ºC, and biocatalyst concentration of 5 wt% (with respect to oil), complete transesterification (> 98% fatty acid methyl ester yield) was achieved in 16 h of reaction duration. The enzyme was amenable to recovery and reuse for the twelve successive catalytic cycles. Moreover, the entrapped enzyme didn’t demand low temperature storage condition and found to be stable and active even after eight months of storage at room temperature (25-30°C). The activation energy for the immobilized enzyme catalyzed ethanolysis and methanolysis were found to be 8.36 and 4.72 kcal mol-1, respectively.
PHD, SCBC
Keywords: Immobilization; Transesterification; Biodiesel; Kinetics